Efek Multiplier Kebijakan Fiskal: Analisis Dampak Program Makan Bergizi Gratis (MBG) Terhadap Struktur Akuntansi Ekonomi Rumah Tangga dan Ketahanan Fiskal Nasional - Inriyanti Assa; Helmin Rumbiak; Galio Burnames; Yulianti Karoma (Fakultas Ilmu Pendidikan Universitas Pahlawan Tuanku Tambusai, 2025)
This study aims to analyze the fiscal policy impact of the Free Nutritious Meal Program (MBG) on macroeconomic multiplier effects and household accounting structures. Specifically, it examines the extent to which MBG creates household cash savings while identifying potential inequalities in fiscal benefits across income groups. This study employed a mixed-methods approach combining quantitative microeconomic analysis and macroeconomic literature review. The quantitative analysis used primary data from 585 households with school-aged children in Keerom Regency, particularly in the Arso area. Pearson’s Chi-Square test was applied to examine the associative relationship between regular household income and the amount of consumption expenditure savings. Meanwhile, the macroeconomic analysis was conducted through a review of empirical literature and national policy evaluation reports related to sectoral multiplier effects, inflation risks, and fiscal sustainability. The findings show a highly significant associative relationship between regular household income and consumption budget savings, with a p-value of 0.000043. At the micro level, fiscal benefits were distributed unequally. Middle- to upper-income households tended to gain larger cash surpluses of more than Rp100,000 per month, while low-income households mostly recorded micro-scale savings of less than Rp50,000 per month. At the macro level, MBG has the potential to stimulate agriculture, food processing, and local MSMEs. However, universal implementation may generate hidden costs, food substitution expenses, demand-pull inflation, and fiscal pressure. MBG can create new household disposable income and stimulate the local food economy. However, universal program design remains vulnerable to budget inefficiency, unequal fiscal benefits, and fiscal sustainability risks.